2021
DOI: 10.1155/2021/5530620
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Clinical Evaluation of Calcaneoplasty with a Balloon System for Calcaneal Fracture at 5 Years of Follow-Up

Abstract: Calcaneal fractures are a challenging clinical problem. Management of this type of injury remains controversial, especially in the context of intra-articular fractures. Surgical treatment with open reduction and internal synthesis (ORIF) is considered the standard treatment for CF, but it is associated with many complications. Several minimally invasive techniques such as balloon-assisted reduction, pin fixation, and tricalcium phosphate augmentation have been proposed to avoid the frequent and recurrent posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The literature shows conflicting results on the outcomes of calcaneus fractures and the potential superiority of one treatment option over another or conservative treatment in those types of fractures [ 7 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows conflicting results on the outcomes of calcaneus fractures and the potential superiority of one treatment option over another or conservative treatment in those types of fractures [ 7 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcaneoplasty was used in achieving promising outcomes in terms of bone healing and complication rates; however, poor evidence studies exist [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the fractures involving intra-articular are challenging injuries to manage because of their complex nature, technical challenges, devastating complications and difficult rehabilitation [ 4 ]. Previous studies have shown that some minimally invasive surgical methods, such as balloon calcaneplasty, arthroscopically assisted reduction and fixation, and percutaneous screw fixation, not only have the same reduction quality and functional outcome as open reduction and internal fixation, but also can reduce the incidence of postoperative complications [ 2 , 5 ]. At the same time, the percutaneous screw fixation (PSF) is a better option, which can not only provide a strong fixation, but also can minimize damage to the surrounding tissues, subsequently result in shorter operative time and hospital stay, and reduced intraoperative blood loss, postoperative pain, and complication rates, specially for Sanders II fractures and a few Sanders III fractures [ 3 , 6 8 ].…”
Section: Introductionmentioning
confidence: 99%